1988
DOI: 10.1007/bf01914351
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and thermal investigations of ammonium heptamolybdate

Abstract: Thermal decomposition of ammonium heptamolybdate was studied by means of differential scanning calorimetry and thermogravimetry. DSC showed that the material decomposes in the temperature region 463-608 K in static air atmosphere, in three steps. The products of decomposition were characterized by IR spectroscopy, elemental analysis and magnetic susceptibility measurements. All the phases are paramagnetic in nature. Kinetic analysis suggested that the first two steps are controlled by a diffusion mechanism, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…4 The thermogravimetric analysis, Differential scanning calorimetry, magnetic susceptibility, elemental analysis and X-ray diffraction data suggest that ammonium cerium sulphate decomposes in continuous flow of oxygen in the following sequence: …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The thermogravimetric analysis, Differential scanning calorimetry, magnetic susceptibility, elemental analysis and X-ray diffraction data suggest that ammonium cerium sulphate decomposes in continuous flow of oxygen in the following sequence: …”
Section: Resultsmentioning
confidence: 99%
“…Thermal investigations of complex compounds are interesting because such studies give understanding of formation of intermediate compounds and mechanism of their formation [1][2][3][4]. Some results of thermogravimetric study of ammonium cerium sulphate have also been reported in literature [5].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a trace of MoO 3 can be seen intact on the left side of the cylinder up to the end of the experiment. The formation of MoO 3 seems to follow the following route as suggested by Sharma and Batra [129]:…”
Section: D Spatial/temporal Cat Type Add Studies Of Alumina Supported...mentioning
confidence: 94%